2014
DOI: 10.1039/c3em00623a
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and transport of PAHs in soil profiles of different water irrigation areas in Beijing, China

Abstract: Vertical distribution characteristics and transport mechanisms of polycyclic aromatic hydrocarbons (PAHs) in soil profiles (0-5.5 m) of different water irrigation areas in the southeast suburb of Beijing were analyzed and compared. 16 priority PAHs on the United States Environmental Protection Agency (US EPA) list were analyzed using gas chromatography and mass spectrometry (GC-MS). The relationship between the properties of soil and PAHs was also studied by statistical analyses. The results showed that total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
3
13
1
Order By: Relevance
“…There was no significant difference in total PAHs concentrations between wastewater and groundwater, explaining the similar profiles of congener between wastewater and groundwater irrigated soils. In the present study, the high PAHs concentrations in surface soils were derived from wastewater, similar as previous studies reported by Jin 6 and Wang 52 . As for PAHs composition, the 2-ring PAHs were the most predominant congener, accounting for 45.24% and 31.88% of the total PAHs in wastewater and groundwater irrigated soils, respectively.…”
Section: Resultssupporting
confidence: 92%
“…There was no significant difference in total PAHs concentrations between wastewater and groundwater, explaining the similar profiles of congener between wastewater and groundwater irrigated soils. In the present study, the high PAHs concentrations in surface soils were derived from wastewater, similar as previous studies reported by Jin 6 and Wang 52 . As for PAHs composition, the 2-ring PAHs were the most predominant congener, accounting for 45.24% and 31.88% of the total PAHs in wastewater and groundwater irrigated soils, respectively.…”
Section: Resultssupporting
confidence: 92%
“…However, in the research of Jin et al . (), Nap showed a phenomenon similar to this study; the Nap content in the topsoil was close to that in the deep soil, and even increased in some deep layers.…”
Section: Resultssupporting
confidence: 88%
“…This is not consistent with the observation in some literature that the surface soil of 0-30 or 40 cm are more likely to adsorb PAHs than deeper soils (Bu et al, 2009;Xiao et al, 2008). However, in the research of Jin et al (2014), Nap showed a phenomenon similar to this study; the Nap content in the topsoil was close to that in the deep soil, and even increased in some deep layers.…”
Section: Distribution Characteristics Of Pahs In the Vadose Zone Profcontrasting
confidence: 99%
See 1 more Smart Citation
“…In China, many predecessors have carried out significant research work on the status of soil PAHs pollution, finding that the pollution status and pollution sources in different regions have obvious differences. However, most of the investigations regarding PAH contamination have usually focused on small scales, including industrial and mining areas, garden green land, and wastewater irrigation sites [13,[37][38][39]. At a national scale, researchers have usually adopted meta-analysis.…”
Section: Introductionmentioning
confidence: 99%